Serum levels and polymorphisms of matrix metalloproteinases (MMPs) in carotid artery atherosclerosis: higher MMP-9 levels are associated with plaque vulnerability. (February 2014) - Silvello, Daiane; Narvaes, Luciane Barreneche; Albuquerque, Luciano Cabral; Forgiarini, Luiz Felipe; Meurer, Luise; Martinelli, Nidiane Carla; Andrades, Michael Everton; Clausell, Nadine; Santos, Kátia Gonçalves dos; Rohde, Luis Eduardo
Abstract Context: Matrix metalloproteinases are involved in atherosclerosis and plaque vulnerability. Objective: To investigate serum levels and genetic polymorphisms of matrix metalloproteinases (MMPs) -1, -3 and -9 in patients submitted to carotid endarterectomy. Methods: Genetic polymorphisms were evaluated using polymerase chain reaction (PCR-RFLP); serum levels were measured using ELISA; histological sections were stained with Picrosirius Red to analyze the fibrous cap thickness, lipid core and collagen content and with hematoxylin--eosin to detect the presence of intraplaque hemorrhage. Results: MMP-9 serum levels were significantly higher in patients with a thinner fibrous cap (p = 0.033) or acute or recent intraplaque hemorrhage (p = 0.008) on histology, as well as in patients with previous stroke (p = 0.009) or peripheral vascular disease (p = 0.049). No consistent associations were observed between different MMP genotypes and fibrous cap thickness, lipid core, collagen content or intraplaque hemorrhage. Conclusions: MMP-9 serum levels were consistently associated with markers of carotid atherosclerosis and lesion vulnerability, whereas specific MMP genotypes were not.